2018
DOI: 10.1177/1941738118818060
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Return to Sport After Pectoralis Major Tendon Repair: A Systematic Review

Abstract: Context:Pectoralis major tendon ruptures are becoming increasingly common due to the growing prevalence of active lifestyles. Studies investigating the efficacy of pectoralis major tendon repair have limited sample sizes and offer mixed results, while existing reviews do not explore postoperative activity outcomes for patients.Objective:To summarize and synthesize the clinical outcomes and rate of return to activity after isolated pectoralis major tendon repair.Data Sources:Four databases (MEDLINE, EMBASE, Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 43 publications
3
48
1
1
Order By: Relevance
“…4,21 Pooled data from a recent systematic review demonstrated 90% return to sport, 74% return to preinjury level of sport, and 95% return to work. 25 There is some discrepancy with respect to the present data; however, pooled analysis incorporates a great deal of heterogeneity from variable surgical technique, follow-up, and patient population. 25…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…4,21 Pooled data from a recent systematic review demonstrated 90% return to sport, 74% return to preinjury level of sport, and 95% return to work. 25 There is some discrepancy with respect to the present data; however, pooled analysis incorporates a great deal of heterogeneity from variable surgical technique, follow-up, and patient population. 25…”
Section: Discussionmentioning
confidence: 70%
“…25 There is some discrepancy with respect to the present data; however, pooled analysis incorporates a great deal of heterogeneity from variable surgical technique, follow-up, and patient population. 25…”
Section: Discussionmentioning
confidence: 70%
“…Operative treatment of PM tears is recommended for both complete and partial injuries in this population due to occupational requirements and has been reported to result in good clinical outcomes. 9,20,25 Various operative techniques are available for repair depending on the severity of the tear and the location of the tear within the musculotendinous unit. The ability of an MRI to accurately identify these characteristics would lead to improved patient counseling preoperatively as well as improved preoperative surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…Functional outcomes and return to military duty rates after this surgery are excellent and in line with findings of large nonmilitary outcomes studies. 4 , 31 Nute et al 20 reported a 94% return to full duty rate and 5.4% reoperation rate in a large study of 257 military patients, while Balazs et al 3 reported a 95.3% return to full duty rate in a study of 214 military patients. We observed a similar trend in this study, with all 13 patients returning to full duty at a mean of 6 months after injury and only 1 patient indicating he was not satisfied.…”
Section: Discussionmentioning
confidence: 99%